The role of the pharmacist in the management of type 2 diabetes: current insights and future directions - Hughes JD; Wibowo Y; Sunderland B; Hoti K (Dove Medical Press, 2017)
Jeffery David Hughes,1 Yosi Wibowo,2 Bruce Sunderland,1 Kreshnik Hoti1,3 1School of Pharmacy, Curtin University, Perth, WA, Australia; 2Centre for Medicines Information and Pharmaceutical Care (CMIPIC), Faculty of Pharmacy, Universitas Surabaya, Surabaya, Indonesia; 3Department of Pharmacy, Faculty of Medicine, University of Prishtina, Prishtina, Kosovo Abstract: Type 2 diabetes is a chronic disease occurring in ever increasing numbers worldwide. It contributes significantly to the cost of health globally; however, its management remains in the most part less than optimal. Patients must be empowered to self-manage their disease, and they do this in partnership with health care professionals. Whilst the traditional role of the pharmacist has been centered around the supply of medicines and patient counseling, there is an evergrowing body of evidence that pharmacists, through a range of extended services, may contribute positively to the clinical and humanistic outcomes of those with diabetes. Further, these services can be delivered cost-effectively. This paper provides a review of the current evidence supporting the role of pharmacists in diabetes care, whilst providing a commentary of the future roles of pharmacists in this area. Keywords: pharmacy, interventions, outcomes, benefits, glycemic control, cost-effectiveness